Estimation of health impacts and externality costs with the robust uniform world model in the Muara Karang generation units - Kumalaningrum, Della; Dalimi, Rinaldy (Universitas Negeri Padang, 2023)
To encourage national economic growth, efforts are made to maintain electricity availability in Indonesia. Until now, the need for electrical energy in Indonesia is still supplied by fossil fuel power plants, especially Steam Power Plants and Gas Steam Power Plants. One of the negative impacts arising from electricity generation activities is air pollution. Air pollution is produced in the form of waste gases such as PM10, SO2, NO2, and these gases causes global warming and impact of human health. In this study, the magnitude of the negative impact calculated based on the impact on public health, which will then be limited to economic value (cost of externalities). Cost of externalities are conditions when the effect of the production of goods or services imposes costs or benefits on other parties, and these costs are not reflected in the price charged for the goods or services produced. The estimation of public health impacts and externality costs calculated in this study comes from power plants operating at the Muara Karang Generation Unit using Robust Uniform World Model (RUWM). The research results show that the amount of health and externality costs obtained for each power plant are different because each power plant has different operating conditions. In PLTGU Block 1, the resulting externality cost was 18,51 cents USD/kWh, PLTGU Block 2 was 3,05 cents USD/kWh, and PLTGU Block 3 was 1,75 cents USD/kWh. The two Unit of PLTU Muara Karang generate different externality costs, namely 1,52 cents USD/kWh for PLTU Unit 4 and PLTU Unit 5 of 1,10 cents USD/kWh.